Implementasi kearifan lokal dalam P5 sebagai upaya pembentukan karakter kewarganegaraan - Annisa Nur Khasanah; Fadhil Purnama Adi (Universitas Sebelas Maret, 2026)
This study aims to explore the implementation of local wisdom in the Pancasila Student Profile Strengthening Project (P5) as an effort to form civic disposition of Grade V Students of SD Negeri 1 Sewurejo and describe the values of civic disposition of Grade V Students of SD Negeri 1 Sewurejo in the implementation of local wisdom in the Pancasila Student Profile Strengthening Project (P5). This study uses a qualitative approach. The method used in this study is the case study method. Data collection techniques in this study were observation, interviews, and document studies. The subjects in this study were educators and grade V students at SD Negeri 1 Sewurejo. The results show that the implementation of P5 consists of the introduction, implementation, and celebration stages with the civic disposition formed being private characters in the form of responsibility, empathy, and optimism, as well as public characters in the form of democratic abilities, social care, and environmental care. The implementation of the